2010
DOI: 10.1677/erc-10-0017
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum level of early prostate cancer antigen is associated with subsequent cancer risk in men with high-grade prostatic intraepithelial neoplasia

Abstract: Early prostate cancer antigen (EPCA) has been recently suggested as a novel biomarker in malignant and premalignant lesions of the prostate. This study was to examine serum expression of EPCA and to further clarify the relationship between initial serum EPCA levels and the presence of subsequent cancer in the individuals with isolated high-grade prostatic intraepithelial neoplasia (HGPIN). An indirect ELISA was used for initial serum EPCA measurement in 112 men with isolated HGPIN, who were enrolled and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Markers in biological fluids have also been described. For example, an increased serum level of early prostate cancer antigen (EPCA) has been associated with a higher cancer risk in men with isolated HGPIN .…”
Section: Introductionmentioning
confidence: 99%
“…Markers in biological fluids have also been described. For example, an increased serum level of early prostate cancer antigen (EPCA) has been associated with a higher cancer risk in men with isolated HGPIN .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of PSCA are also amplified in the prostate intraepithelial neoplasia (PIN) lesions that 5 in patients undergoing radical prostatectomy, however only 46 blood samples were examined (Paul et al, 2005). ELISA used for initial serum EPCA measurement in 112 men with isolated high-grade prostatic intraepithelial neoplasia (HGPIN), showed a significantly higher serum ECPA level in isolated HGPIN patients with subsequent cancer than those without cancer (Zhao & Zeng, 2010). Pretreatment serum EPCA levels were also determined with an ELISA in 77 patients with clinically localized prostate cancer who underwent radical prostatectomy and 51 patients with locally advanced or metastatic disease who received primary androgen deprivation therapy, and were correlated with clinicopathological variables and disease progression.…”
Section: Prostate Stem Cell Antigen (Psca)mentioning
confidence: 99%
“…They found that mean plasma EPCA level in the patients with PCa was significantly higher than each of the other populations, and that the plasma EPCA, at a cutoff of 1.7 absorbance at 450 nm, had a sensitivity of 92% (11/12) for PCa patients, a specificity of 100% (16/16) for healthy donors, and an overall specificity of 94% (32/34) for entire donor controls. In two recent studies, we measured the EPCA levels in serum from men with isolated high-grade prostatic intraepithelial neoplasia (HGPIN) [20] and men with symptomatic benign prostatic hyperplasia (BPH) who underwent transurethral resection of the prostate (TURP) [21]. We found that elevated serum levels of EPCA were significantly correlated with increased risk of the subsequent PCa onset in HGPIN during a period of ≥5 years follow-up and the incidental PCa presence on TURP specimens analysis.…”
Section: Introductionmentioning
confidence: 99%